Effect of compression waveform and resuscitation duration on blood flow and pressure in swine: One waveform does not optimally serve. (October 2018) - Lampe, Joshua W.; Yin, Tai; Bratinov, George; Kaufman, Christopher L.; Berg, Robert A.; Venema, Alyssa; Becker, Lance B.
Abstract: Background: Chest compression (CC) research primarily focuses on finding the 'optimum' compression waveform using a variety of compression efficacy metrics. Blood flow is rarely measured systematically with high fidelity. Using a programmable mechanical chest compression device, we studied the effect of inter-compression pauses in a swine model of cardiac arrest, testing the hypothesis that a single 'optimal' CC waveform exists based on measurements of resulting blood flow. Methods: Hemodynamics were studied in 9 domestic swine (∼30 kg) using multiple flow probes and standard physiological monitoring. After 10 min of ventricular fibrillation, five mechanical chest compression waveforms (5.1 cm, varying inter-compression pauses) were delivered for 2 min each in a semi-random pattern, totaling 50 compression minutes. Linear Mixed Models were used to estimate the effect of compression waveform on hemodynamics. Results: Blood flow and pressure decayed significantly with time in both arteries and veins. No waveform maximized blood flow in all vessels simultaneously and the waveform generating maximal blood flow in a specific vessel changed over time in all vessels. A flow mismatch between paired arteries and veins, e.g. abdominal aorta and inferior vena cava, also developed over time. The waveform with the slowest rate and shortest duty cycle had the smallest mismatch between flows after about 30 min of CPR. Conclusions: This data challenges the concept of a single optimal CC waveform. Time dependent physiological response to compressions and no single compression waveform optimizing flow in all vessels indicate that current descriptions of CPR don't reflect patient physiology.